2014
DOI: 10.3174/ajnr.a4172
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolic Abnormalities Associated with Developmental Venous Anomalies

Abstract: BACKGROUND AND PURPOSE:Developmental venous anomalies are the most common intracranial vascular malformation and are typically regarded as inconsequential, especially when small. While there are data regarding the prevalence of MR imaging findings associated with developmental venous anomalies, FDG-PET findings have not been well-characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…26 In a study of 25 DVAs, Larvie et al found that 76% had metabolic abnormalities on PET scans in the adjacent brain parenchyma most commonly in the form of glucose hypometabolism, which was more severe in older patients. 27 An important point regarding the above-mentioned studies is that most of the DVAs with associated abnormality in the adjacent brain parenchyma on physiologic imaging techniques did not have any structural brain abnormalities. Therefore, the elevation of perfusion parameters and hypometabolism associated with DVAs may indicate that DVAs are less robust than normal venous drainage pathways 26 with resultant diminished venous drainage capacity.…”
Section: Drainage and Anatomic Locationmentioning
confidence: 96%
See 1 more Smart Citation
“…26 In a study of 25 DVAs, Larvie et al found that 76% had metabolic abnormalities on PET scans in the adjacent brain parenchyma most commonly in the form of glucose hypometabolism, which was more severe in older patients. 27 An important point regarding the above-mentioned studies is that most of the DVAs with associated abnormality in the adjacent brain parenchyma on physiologic imaging techniques did not have any structural brain abnormalities. Therefore, the elevation of perfusion parameters and hypometabolism associated with DVAs may indicate that DVAs are less robust than normal venous drainage pathways 26 with resultant diminished venous drainage capacity.…”
Section: Drainage and Anatomic Locationmentioning
confidence: 96%
“…Sharma et al investigated 24 patients with 25 DVAs using dynamic susceptibility contrast (DSC) perfusion MRI and demonstrated that normal‐appearing brain parenchyma surrounding DVAs showed a marked increase in relative cerebral blood volume), and increased relative mean transit time, compared to the contralateral normal‐appearing brain (Figs and ) . In a study of 25 DVAs, Larvie et al found that 76% had metabolic abnormalities on PET scans in the adjacent brain parenchyma most commonly in the form of glucose hypometabolism, which was more severe in older patients . An important point regarding the above‐mentioned studies is that most of the DVAs with associated abnormality in the adjacent brain parenchyma on physiologic imaging techniques did not have any structural brain abnormalities.…”
Section: Neuroimaging Findings: Advanced Mri and Petmentioning
confidence: 99%
“…Multiple imaging examples of parenchymal and perfusion abnormalities associated with DVAs have been documented [ 9 ]. We previously showed the presence of a mild, moderate, or severe degree of DVA-associated hypometabolism (DVAAh) in 72% (18 of 25) of the DVAs in patients who had a known DVA and FDG-PET imaging [ 10 ]. A quantitative analysis of DVAAh, however, has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…(6, 7) Developmental venous anomalies, the most common intracranial vascular abnormality and more common in children with brain tumors,(8) consist of abnormally dilated veins converging on a larger draining vein, and have been associated with parenchymal signal abnormalities, elevated rCBV, mean transit time and venous stasis. (911) Though the precise mechanism is unknown, our observations in this series suggest that increases in rCBV due to increased regional vascular density or venous congestion associated with DVAs may facilitate active or passive transendothelial transport of radiotracer, followed by preferential uptake of 11 C-Met by the more metabolically active cortex in the venous drainage territories, accounting for the disproportionately cortical uptake we observed. Thus, observation of elevated 11 C-Met uptake and rCBV, particularly in a somewhat discrepant distribution, should prompt close review of contrast-enhanced MRI to evaluate for a potentially vascular etiology prior to biopsy.…”
mentioning
confidence: 73%